On asymptotics of a population model with random mating - Skakauskas, Vladas (Mathematical Modelling and Analysis, 1997)
This paper deals with a model for an age‐sex structured population consisting of male, single and fertilized female subclasses taking into account a random coupling of sexes (for a period of mating only) and females’ pregnancy. For certain forms of the demographic rates there are presented separable solutions, and the asymptotic behaviour of the general solution is demonstrated.First Published Online: 14 Oct 2010